2017
DOI: 10.1590/1807-7692bar2017170025
|View full text |Cite
|
Sign up to set email alerts
|

Does Operational Risk Disclosure Quality Increase Operating Cash Flows?

Abstract: This study aims to measure the degree of operational risk disclosure and examine its impact on operating cash flow of banks listed on the UAE Abu Dhabi Stock Exchange (ADX) and Dubai Financial Market (DFM) during the period 2003-2016. The authors conducted content analysis of the annual reports to measure the degree of operational risk disclosure. In addition, they used dynamic panel data regressions to analyze the impact of operational risk disclosure on the operating cash flow generated by the banks. The res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 13 publications
1
3
0
Order By: Relevance
“…Thus, CSR does not add significant value to the willingness of banks to disclose any financial information. These findings corroborate the findings of [80], who suggested that the scope of CSR is restricted to achieving significant disclosure of the business, especially in financial reporting. Therefore, the directors of commercial banks must determine the suitability of their actions for the public, bringing stability, harmony, and strength to society.…”
Section: Discussionsupporting
confidence: 90%
“…Thus, CSR does not add significant value to the willingness of banks to disclose any financial information. These findings corroborate the findings of [80], who suggested that the scope of CSR is restricted to achieving significant disclosure of the business, especially in financial reporting. Therefore, the directors of commercial banks must determine the suitability of their actions for the public, bringing stability, harmony, and strength to society.…”
Section: Discussionsupporting
confidence: 90%
“…According to stakeholder theory, an organization should transparently report all its CSR activities to maintain a sustainable connection with stakeholders (Nobanee and Ellili, 2017a). This extends legitimacy theory, which assumes inherent communication among organizations besides society, in which they must report their CSR activities to prove the fulfillment of their part in the contract and compliance with the value systems of the society (Adel et al , 2019).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Disclosure quality (DQ) does not have a global, qualitative or quantitative definition. Nevertheless, researchers such as (Nobanee and Ellili 2017) note that disclosure quality concerns the information's relevence to numerous external parties; moreover, it should be available for audit. Disclosure quality is based on the utility of the information to interested users regarding informed decision-making (De Luca et al 2020).…”
Section: Disclosure Qualitymentioning
confidence: 99%